Microstructural Characterization of AlCrTiV – Si High Entropy Alloy for advanced applications - Daskalopoulos Ioannis (EDP Sciences, 2021)
This work deals with the microstructural characterization of two equiatomic high-entropy, low-density alloys (HEA), the AlCrTiV and AlCrTiV-Si7.2. These alloys can serve as potential candidates for advanced applications where high strength and enhanced ductility is demanded. For ensuring high ductility the alloys must contain as minimum as possible hard precipitates. As the strength increase is based on both solid solution and precipitation hardening, the laboratory made alloys were investigated in as-cast and heat-treated conditions. For the heat treatment a high soaking temperature of 1200°C for 8 hours was selected to ensure microstructure homogenization. Micrographic observations of the AlCrTiV and AlCrTiV-Si7.2 samples in the as-cast condition indicated the presence of a dendritic microstructure. Furthermore, chemical micro-analysis showed segregation in the matrix in both samples. This is a critical result as this segregation will lead to heavy precipitation at interdendritic regions, it may sensitize these regions and in the worst-case scenario may cause cleavage fracture in the micro scale, which can trigger brittle fracture during cooling even without the application of deformation. However, the selected heat treatment eliminated the segregation phenomena forcing the alloying elements to be uniformly distributed in the matrix. At the center of the heat-treated AlCrTiV-Si7.2 sample the fragmentation and spheroidization of the intermetallic phase Ti5Si3 was observed. For the same sample, at the mold-sample’s interface, the particles Ti5Si3 were shown to dissolve and form aggregates. Both alloys exhibited high hardness values with small differences between the as-cast and heat-treated conditions, which indicates that the AlCrTiV–Si7.2 high entropy alloy presents high yield strength and may operate at high temperatures without deterioration of the mechanical properties nor unexpected failure.